(untitled) (Journal of Entrepreneurship and Business, 2022)
The focus of this research is the practice of buying and selling online credit systems and their conformity with Islamic law. The purpose of this study is to find out how the views and Islamic law on the Online Credit Buying and Selling System and how the impact on the community of the online credit buying and selling system. This type of research is qualitative research. This research is a type of research that seeks to develop concepts, understandings, and theories from field conditions and in the form of descriptions. The technique used in data collection is interviews and written data, such as books, articles, and others that are used to obtain data about the online credit buying and selling system and its compatibility with Islamic law. The results of this study are the Indonesian people already know the existence of this online credit. However, modern facilities that facilitate online loan transactions leave many problems in society, starting from the practice of usury. In addition, there is also the threat of spreading private secrets to the public through social media.